The relationship between agency cost and managerial equity ownership in small firms / Nurul Fatma Aziz ... [et al.] - Aziz, Nurul Fatma; Mohd Sallem, Nur Raihana; Mohd Nasir, Noor Emilina; Jasni, Nur Syuhada; Mohd Zam, Zuraidah; Yaacob, Najihah Marha (2013)
Despite contradicting views regarding the role of managerial equity ownership (MEO) in reducing agency cost, some evidences from both the United States (US) and United Kingdom (UK) document that this corporate governance mechanism has a significant relationship with the agency cost (Ang, Cole and Lin, 2000; Sing and Davidson, 2003; Florackis, 2008; and Mcknight and Wier, 2009). This study attempts to compare the relationship between MEO and agency cost of small firms in Malaysia. This study used return on assets (ROA), asset utilisation ratio (AUR) and selling, general and administration (SGA) expense ratio (Exp) as a proxy for agency cost. Using a sample of 78 companies listed on Bursa Malaysia, this study used a regression model to test the relationship. The regression results have provided evidences that MEO possessed a significant impact in reducing the agency cost depending on the size of the firms. This study found that ROA was significantly positively associated with MEO in small firms. Meanwhile, MEO significantly alleviated principal agent conflicts in small firms through efficient use of assets that resulted in a high AUR. The findings of this study are expected to guide managers to determine the right MEO for the company, which depends on the firm's size. Investors would be able to use the results as a basis to make investment decision since the analysis of the findings showed that MEO affected the performance and operations of the company.